Reclaiming and Redefining Research - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2020)
Action research, practitioner inquiry, self-study, scholarship of teaching and learning, or practice-based research – there are numerous names for this work. Yet, whether you are new to action research or a veteran of classroom inquiry, I hope this issue of Networks continues to inspires you to “reflect on classroom practice through research ventures… alone or in collaboration, use inquiry as a tool to learn more about your work with the hope of eventually improving its effectiveness” (from the mission statement of Networks: An Online Journal for Teacher Research).